PROMOTING PT. ANEKA INDO MAKMUR AND ITS PRODUCTS USING A COMPANY PROFILE VIDEO - Amelia Abrianti; Jusuf I Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2017)
This Business Communication Final Project (BCFP) is made for PT. Aneka Indo Makmur (AIM), one of the biggest biscuits manufacturers in Indonesia. The background of the study is the fact that the company has a hard time getting new partners or distributors. PT. AIM does not have a right promotional tool that can convince the partners to work together with the company. Because of this problem, the company cannot develop the business. Thus, PT. AIM needs a company profile video which not only can give a clearer information about the company, but also can function as a marketing tool for PT. AIM, to promote its unique strengths and attract more partners or distributors. This company profile video contains the company’s history, product description, structure of the company, employee performance, company’s vision and mission statement, company’s working environment, and also rewards that the company has received.